Understanding Malaysian Preference for Local Beef - Harun, Amran; Hamir, Mohd Indra Bin; Farradia, Yuary; Maged Othman, Bestoon Abdul (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
In Malaysia, the demand for beef outsprints its supply. This issue has led to an unstainable over-reliance on imports and consequently has brought to the issues of steep prices to end consumers. Part of the problem is a poor understanding of the beef buying preferences of consumers and the factors that shape the preferences. This study sought to determine the key factors influencing consumer buying preferences for beef among Malaysian, particularly examining the effects of price and quality. A cross-sectional survey of 384 beef consumers drawn from social media platforms was undertaken. Data was collected using a structured questionnaire and analyzed using SPSS. All factors were found to have a significant positive effect on beef buying preferences among consumers in Malaysia. It is recommended that firms in the beef industry consider these factors in their beef production and marketing